DEVELOPING LITERARY PRONUNCIATION IN PRIMARY GRADES - Uzoqova Durdona Muratali qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The article highlights the significant role of literacy and reading lessons in developing pronunciation exercises for primary school students. It emphasizes the systematic use of exercises and tasks during native language lessons that foster speech skills and guide students toward correct pronunciation.